PENANAMAN MODAL DALAM NEGERI DAN INFLASI PENGARUHNYA TERHADAP PRODUK DOMESTIK REGIONAL BRUTO PROVINSI JAWA TIMUR - Norida, ; Arif Indrayanto P, (Pendidikan Ekonomi, 2010)
The purpose of the present research was to find out the effect of domestic investment and inflation on gross domestic regional product of East Java. The population of the study was the domestic investment, inflation, and gross domestic regional product of East Java, whereas the sample was the value of domestic investment, inflation, and gross domestic regional product of East Java in 1998-2007. The data collection technique was documentation. Statistical analyses of multiple linier regression and correlation were used in the data analysis. The results showed that the domestic investment and inflation simultaneously had a significant impact on gross domestic regional product of East Java. Moreover, inflation was the more dominant factor affecting the gross domestic regional product of East Java.